2011
DOI: 10.1016/j.toxlet.2011.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Airborne polychlorinated biphenyls (PCBs) reduce telomerase activity and shorten telomere length in immortal human skin keratinocytes (HaCat)

Abstract: PCBs, a group of 209 individual congeners, are ubiquitous environmental pollutants and classified as probable human carcinogens. One major route of exposure is by inhalation of these industrial compounds, possibly daily from inner city air and/or indoor air in contaminated buildings. Hallmarks of aging and carcinogenesis are changes in telomere length and telomerase activity. We hypothesize that semi-volatile PCBs, like those found in inner city air, are capable of disrupting telomerase activity and altering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 62 publications
0
44
2
Order By: Relevance
“…Our results are inconsistent with the findings of prior in vitro studies that observed telomere shortening because of exposure to PCB 153, PCB 126, PCB 52, PCB 28, or 2-(4′-chlorophenyl)-1, 4-benzoquinone (PCB3pQ) (Jacobus et al, 2008; Senthilkumar et al, 2011; Senthilkumar et al, 2012; Xin et al, 2016; Ziegler et al, 2016). Alternative mechanisms by which PCBs may induce telomere lengthening have been proposed (Scinicariello and Buser, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are inconsistent with the findings of prior in vitro studies that observed telomere shortening because of exposure to PCB 153, PCB 126, PCB 52, PCB 28, or 2-(4′-chlorophenyl)-1, 4-benzoquinone (PCB3pQ) (Jacobus et al, 2008; Senthilkumar et al, 2011; Senthilkumar et al, 2012; Xin et al, 2016; Ziegler et al, 2016). Alternative mechanisms by which PCBs may induce telomere lengthening have been proposed (Scinicariello and Buser, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…In vitro , immortalized human skin keratinocytes, hamster lung fibroblasts, immortalized lymphocytes, or human promyelocytic leukemia cells exposed to PCB 153, PCB 126, PCB 52, PCB 28, or 2-(4′-chlorophenyl)-1, 4-benzoquinone (PCB3pQ), have shortened telomeres (Jacobus et al, 2008; Senthilkumar et al, 2011; Senthilkumar et al, 2012; Xin et al, 2016; Ziegler et al, 2016). Conversely, PCB 138 and PCB 153 upregulate c- myc in vitro (Ghosh et al, 2007; Gribaldo et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…ROS are also able to reduce telomerase activity which can determine telomere shortening. The contribution of all or part of these alterations may facilitate the onset of tumors and more specifically HCC [200][201][202][203][204][205] . At present we have no conclusive data on the relationship between PCBs and HCC and further studies will be needed to establish the causal link.…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Subsequent publications on air pollution and skin aging from 2011 through 2014 demonstrated that: (a) airborne polychlorinated biphenyls (PBCs) reduced telomerase activity and shorten telomere length in human skin (HaCat) keratinocytes [44]; (b) free radicals and organic nanoparticles reduced human keratinocyte viability by apoptosis [43,45,46]; (c) eczema increased with exposure to PM of 10 microns or less in office indoor environments [47] and; (d) atopic dermatitis and other skin sensitivities or aging endpoints increased with air pollutants that are known to induce increased levels of ROS [48][49][50].…”
Section: Air and Water Pollution And The Generation Of Rosmentioning
confidence: 99%